Market Driven Political Advertising Social, Digital and Mobile Marketing - Hughes, Andrew (Palgrave Studies in Political Marketing and Management, 2018)
Exploring the new era of political advertising beyond television and print, this book focuses on the mediums of the new millennia that are transforming campaigning and communications in political systems around the world. The author illustrates how the use of social, digital and mobile advertising enables political marketers to deliver messages more accurately and strengthen relationships between stakeholders such as voters, supporters and candidates. Examining digital and social media platforms such as Facebook, Twitter and YouTube, this innovative book analyses the changing political marketing landscape and proposes conceptual models for implementing more successful and effective political communications in the future. .